2016
DOI: 10.1016/j.apenergy.2016.02.118
|View full text |Cite
|
Sign up to set email alerts
|

Day-ahead hourly electricity load modeling by functional regression

Abstract: Short-term load forecasting is important for power system generation planning and operation. For unit commitment and dispatch processes to incorporate uncertainty, a short-term load model must not only provide accurate load predictions but also enable the generation of reasonable probabilistic scenarios or uncertainty sets. This paper proposes a temporal and weather conditional epi-splines based load model (TWE) using functional approximation. TWE models the dependence of load on time and weather separately by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…The empirical results showed that the proposed model performs better and was able to capture the effects that the French's operational model could not capture [34]. Using functional approximation, [12] developed a day-ahead hourly electricity forecasting model. The developed model uses weather forecasts and also captures temporal patterns.…”
Section: An Overview Of the Literature On Load Forecastingmentioning
confidence: 99%
“…The empirical results showed that the proposed model performs better and was able to capture the effects that the French's operational model could not capture [34]. Using functional approximation, [12] developed a day-ahead hourly electricity forecasting model. The developed model uses weather forecasts and also captures temporal patterns.…”
Section: An Overview Of the Literature On Load Forecastingmentioning
confidence: 99%
“…For example, Bessec and Fouquau [19] developed an one day-ahead forecast for half-hourly electricity loads using a combination of stationary wavelet transformations that yielded 502 daily observations for each half-hour in France. Based on the corresponding weather forecasts, Feng and Ryan [20] provided accurate day-ahead hourly load forecasting for multiple zones within a region using a temporal and weather conditional epi-splines-based load models. Tong et al [21] developed a deep learning based model and established a support vector regression model to forecast the total day-ahead electricity load, and then refined the features by stacking the denoising auto-encoders with historical electricity load data and related temperature parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Although SARIMA models are easy to use and are capable of forecasting accurately, they have some limitations. The machine learning methods such as artificial neural networks (ANNs) and support vector regression (SVRs) are restricted to specified functions [20]. The SVR-based electricity load forecasting methods are proposed and show good performance mainly due to the strong non-linear learning capability of SVR.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate STLF predictions play a vital role in electrical department load dispatch, unit commitment, and electricity market trading [1]. With the permeation of renewable resources in grids and the technological innovation of electric vehicles, load components become more complex and make STLF difficult; therefore, strict requirements of stability and accuracy are needed [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%